Autopsy and genetic characterization of juvenile sudden cardiac arrest and death: the ToRSADE experience. (10th June 2022) - Spinelli, V; Girolami, F; Maurizi, N; Grifoni, R; Maio, V; Focardi, M; Albora, G; Nesi, G; Coppini, R; Cerbai, E; Olivotto, I
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): FAS-Salute 2014, regione Toscana Background: Sudden cardiac arrest (SCA) or death (SCD) in young people represents a dramatic event, often leading to severe neurologic outcomes or death. However, the incidence of this phenomenon remains largely unknown, since the recording of cases, and consequently the identification of the underlying causes, requires a multi-professional and disciplinary approach, including genetic counselling. Purpose: In this study, we aimed to monitor and investigate SCA and SCD in young people (≤50 years) recorded in the ToRSADE© registry comparing clinical and molecular data. Methods and Results: A total of 22 blood samples were analyzed; 14 were collected from dead patients during autopsy and 8 from resuscitated patients after cardiac arrest. Next Generation Sequencing (NGS) analysis revealed 38% of total cases with Likely Pathogenetic (LP) variants associated to Cardiomyopathy (CM) or Channelopathy, and 61% with Variant of Uncertain Significance (VUS). In three cases, NGS confirmed autopsy and histology findings: the p.(Leu466Phe) variant in SCN5A associated with Brugada Syndrome (1a), the p.(Glu173del) in TNNT2 for Hypertrophic CM (1b) and the p. (Asn480Lysfs*20) in PKP2 for Arrhythmogenic Cardiomyopathy (AC) (1c). Conclusions: Creation of the ToRSADE© registry allowed implementation of a blood repository for molecular and genetic analysis. Genetic analysis combined with clinical information and post-mortem evaluation constitute a multi-disciplinary approach to juvenile SCD and SCA, while providing medical and genetic assistance to families, public awareness especially among youths and athletes, as well as up-to-date research on the underlying mechanisms of cardiomyopathies.